Comparative Analysis of Conventional Taxi Performance with Application-Based Taxi in Batam - Jason Angelo Ong; Andri Irfan Rifai; Susanty Handayani (International Journal Labs, 2022)
Public transportation has become an alternative for people in their daily activities. As technology develops, online public transportation or application-based online taxis emerges. The purpose of this paper is to find out the performance between conventional taxis and online taxis. The authors used the Importance Performance Analysis (IPA) method in this study. Before being able to use the IPA method, the author will first collect data by opening a questionnaire with a minimum of 100 respondents for analysis. The study's findings indicate that online taxis perform better than conventional taxis. However, in the importance perception, conventional taxis also get a lower average value than online taxis.